Thermal post-treatment and material characterization of laser powder bed fusion additively manufactured Ti-6Al-4V - Anand Abhinav; Devarajan Nagarajan; Gupta Rohit Kumar; Kamboj Nikhil; Ganvir Ashish (United Kingdom, 2025)
Laser powder bed fusion of Ti-6Al-4V (PBF-LB/Ti-6Al-4V) alloy results in the formation of non-equilibrium microstructures due to very high cooling rates, causing them to be unfit for direct applications; therefore, post-heat-treatment operations are required. This paper investigates the effects of different heat treatment operations on the microstructure, hardness and phase composition of as-built PBF-LB/Ti-6Al-4V samples. Six sets of heat-treatment operations have been designed in which samples have been first subjected to either above or below the beta (β) transus zone of 980 °C, then subjected to air cooling or water quenching followed by ageing at 510 °C. The novelty of this article is performing double quenching on as-built Ti-6Al-4V parts. Optical microscopy, Vickers microhardness testing, and XRD analysis have been performed on heat-treated samples for material characterization. Microstructural studies have revealed that depending upon the cooling medium and subjected temperature during heat treatment, the extent of dissolution of martensitic (α') needle-like phases present in as-built samples into α-β phase varies, resulting in variation of hardness values. XRD analysis confirmed the presence of β-phase along with the α-phase in the matrix in air-cooled heat-treated samples. Maximum hardness was obtained in the case when the sample was solutionized at 1050 °C, followed by water quenching and ageing due to the formation of intermetallic precipitates.
NOLAMP- Nordic Laser Materials Processing Conference (19TH-NOLAMP-2023)